2009
DOI: 10.1088/0953-8984/21/23/235604
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of quantum criticality in CeNi9−xCuxGe4

Abstract: Crystal structure, specific heat, thermal expansion, magnetic susceptibility and electrical resistivity studies of the heavy fermion system CeNi(9-x)Cu(x)Ge(4) (0≤x≤1) reveal a continuous tuning of the ground state by Ni/Cu substitution from an effectively fourfold-degenerate non-magnetic Kondo ground state of CeNi(9)Ge(4) (with pronounced non-Fermi-liquid features) towards a magnetically ordered, effectively twofold-degenerate ground state in CeNi(8)CuGe(4) with T(N) = 175 ± 5 mK. Quantum critical behavior, [… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
43
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(52 citation statements)
references
References 39 publications
8
43
1
Order By: Relevance
“…For CeNi 8.8 Fe 0.2 Ge 4 the upper maximum increases and remains at the same temperature while the Kondo-type anomaly decreases as it is also observed in the homologous CeNi 8.8 T 0.2 Ge 4 (T: Co, Cu) [12,13]. This common behavior at lowest level of substitution is most likely a consequence of disorder introduced in the pseudo-ternary solid solution.…”
Section: Resultssupporting
confidence: 53%
See 4 more Smart Citations
“…For CeNi 8.8 Fe 0.2 Ge 4 the upper maximum increases and remains at the same temperature while the Kondo-type anomaly decreases as it is also observed in the homologous CeNi 8.8 T 0.2 Ge 4 (T: Co, Cu) [12,13]. This common behavior at lowest level of substitution is most likely a consequence of disorder introduced in the pseudo-ternary solid solution.…”
Section: Resultssupporting
confidence: 53%
“…m and m . mm point symmetry, respectively) [12]. This result was later confirmed by neutron powder diffraction experiments and subsequent Rietveld refinements which revealed that "on average each fourth Ni atom at the 16k sites is substituted by copper" [15].…”
Section: Electronic Structure Calculationsmentioning
confidence: 71%
See 3 more Smart Citations